2007
DOI: 10.1152/ajpcell.00301.2006
|View full text |Cite
|
Sign up to set email alerts
|

Proximal tubular epithelial cells are generated by division of differentiated cells in the healthy kidney

Abstract: We searched for evidence for a contribution of stem cells in growth of the proximal S3 segments of healthy rats. According to the stem cell model, stem cells are undifferentiated and slow cycling; the bulk of cycling cells are transit amplifying, rapidly cycling cells. We show the following. 1) By continuous application of a thymidine analog (ThA) for 7 days, S3 proximal epithelial cells in healthy kidneys display a high-cycling rate. 2) Slow-cycling cells, identified by lack of ThA uptake during 14 days of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
83
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 29 publications
10
83
1
1
Order By: Relevance
“…This is consistent with findings of Le Hir and coworkers, who showed that in growing adolescent normal rats, tubular cells undergo cellular divisions while remaining fully differentiated (19,20). In contrast, in human kidneys, we noted that STCs showed a dedifferentiated phenotype with loss of brush border and of the basolateral labyrinth (12).…”
Section: Pec-rtta Mouse Is a Useful Tool To Identify And Manipulate Ssupporting
confidence: 93%
“…This is consistent with findings of Le Hir and coworkers, who showed that in growing adolescent normal rats, tubular cells undergo cellular divisions while remaining fully differentiated (19,20). In contrast, in human kidneys, we noted that STCs showed a dedifferentiated phenotype with loss of brush border and of the basolateral labyrinth (12).…”
Section: Pec-rtta Mouse Is a Useful Tool To Identify And Manipulate Ssupporting
confidence: 93%
“…Such slow clearance would bias our results toward a small increase in double-labeled cells, as has been previously reported (21). The observation that proximal tubule cells undergo cell cycle arrest after division in growing rats is consistent with our low mea- sured frequency of CldU-and Ki67-copositive cells after IRI (18). Taken together, our observations do not support even a minor contribution of specialized intratubular progenitors to epithelial repair.…”
Section: Discussionsupporting
confidence: 80%
“…To accurately quantify two sequential rounds of DNA synthesis in the same cell, we used the thymidine analogs, 5-chloro-2-deoxyuridine (CldU) and 5-iodo-2-deoxyuridine (IdU), in a strategy validated in solid organs, including pancreas (16), heart (17), and adult, uninjured kidney (18). To assess the specificity of CldU and IdU in our renal IRI model, we performed unilateral IRI and killed mice 48 h after injury.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tubular regeneration may be a stochastic process in which the least-injured cells dedifferentiate and repopulate the denuded basal membranes. 4,5 This view has been challenged by the concept of renal and/or bone marrow-derived stem cells participating in the regenerative process. 6 Recent data, however, indicate a minor role for the latter cell type, 7,8 and the search for the defining features of adult tubular stem or progenitor cells has, to date, been inconclusive, with discrepant results regarding their proper histologic markers and their histologic location.…”
mentioning
confidence: 99%